ANTICANCER POTENTIAL OF Î±-MANGOSTIN - Muchtaridi, Muchtaridi; Wijaya, Cindy Aprillianie (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Mangosteen (Garcinia mangostana Linn.) is a tropical fruit originated from South East region. Mangosteen exhibiting a variety of pharmacological activities and is often used for traditional medicine. There are numerous chemical compounds contained in the pericarp of the mangosteen fruit. One of them is xanthone derivative which in some studies shows antioxidant and anticancer activity by preventing free radical and damaging cells. One of the xanthone derivatives that have the strongest anticancer properties is Î±-mangostin. Methods: Anticancer potential of Î±-mangostin was reviewed from available literature. Results: The Î±-mangostin shows anti-proliferative and apoptotic activity by suppressing the formation of carcinogenic compounds in various cancer cells. This review will summarize the anticancer properties of Î±-mangostin that may be exploited for effective cancer prevention. Conclusion: Development of Î±-mangostin as a chemopreventive compound can provide new opportunities for effective cancer drug discovery. Î±-mangostin is useful as a complementary or alternative medicine and a chemopreventive tool against cancer.